Records Keeping and Performance of Small Scale Businesses in Bushenyi District: A Case Study of Bushenyi Town Council. - Allen, Natunkunda (Kabale University, 2019)
A Research Report Submitted to the Faculty of Arts and Social Sciences in Partial Fulfillment of the Requirements for the Award of a Diploma in Records Management of Kabale University.